Menavigasi Pasar Modal Syariah: Pengaruh Komoditas, Makroekonomi, dan Mata Uang Kripto dalam Kerangka Keuangan Islam di Indonesia - Didik Gunawan; Andri Soemitra; Isnaini Harahap (JURNAL ILMIAH GEMA PERENCANA, 2025)
This study examines the dynamic interaction of commodity prices (crude oil, gold, coal), macroeconomic indicators (exchange rates, inflation, interest rates), and cryptocurrencies (Bitcoin, Ethereum) on the Indonesian Islamic stock market, using the Jakarta Sharia Index (JII) as a benchmark. The research method employed a quantitative approach, with a Vector Error Correction Model (VECM) model with weekly data from 2018 to 2024. This study found that crude oil and coal prices have a positive effect on the JII in the short term, while gold acts as a safe haven asset with a negative correlation. Exchange rate depreciation and inflation negatively impact the JII, and interest rates have an indirect effect. Cryptocurrencies exhibit a weak correlation, offer diversification potential but raise Sharia compliance concerns due to speculative risks. These findings contribute to the understanding of the impact of global markets on Islamic investment and provide information to policymakers and investors in aligning strategies with the principles of maqasid Sharia.